Satisfaction with democracy predicts democratic behaviors - Andrés Santos Vargas; Enrique Seira; Alberto Simpser (Proceedings of the National Academy of Sciences, 2026)
The global decline in satisfaction with democracy, as measured in surveys, is sometimes used as evidence of democracy’s precarious health. However, existing evidence on the link between democratic attitudes and behaviors is mostly based on self-reported behaviors or country-level comparisons. We study the link between satisfaction with democracy and democratic behaviors at the individual level with original data consisting of 50,000+ surveys of Mexican citizens matched with individual-level administrative information about three democratic behaviors: attendance to poll worker training, staffing a polling station on Election Day, and turning out to vote a year later. We find that survey-measured dissatisfaction with democracy predicts lower democratic engagement on all three behaviors. Our findings suggest that the global decline in survey-measured satisfaction with democracy is indeed cause for concern.